Automated malnutrition screening in a multisite cancer center. Issue 28 (1st October 2022) - Kadakia, Kunal C.; Szafranski, Michele; Meadors, Patrick L.; Aktas, Aynur; Walsh, Declan
Abstract : 415 Background: Malnutrition (MN) negatively impacts patients' tolerance to anti-cancer therapies and clinical outcomes. Registered dietitian nutritionists (RDNs) are integral to establishing personalized nutritional plans but are a limited resource at cancer centers. The optimal method for operationalizing MN screening and assessment by an RDN is not established. The present study describes the experience of MN screening and automated RDN assessment at Atrium Health's Levine Cancer Institute. Methods: MN screening using the Malnutrition Screening Tool (MST) was added to our institution's electronic distress screening process in May 2017. Automated email alerts to review electronic medical records (EMR) of those with high risk for MN (MST ≥3 of 5; H-MST) before formal RDN evaluation were added in October 2017. RDN reviewed the EMR to identify malnutrition based on internationally accepted guidelines. Here we describe our experience over a 8-month period from May 2019 through December 2019. Results: Among 4009 unique patients who completed the MST, 2953 (74%) had a score of 0-2, 1056 (26%) had H-MST with scores of 3, 4, and 5 in 514 (13%), 349 (9%), and 193 (5%), respectively. Among H-MST screens, automated RDN evaluation occurred in 512 (48%). EMR review by the RDN revealed that 242 (47%) met MN criteria for formal RDN evaluation. The reasons for exclusion from formal RDN evaluation included no weight loss documented (114, 22%), non-malignant condition (107, 21%), and others (49, 10%) (deceased, hospitalized, no reason listed, or enrolled in hospice). Of those who were planned for formal RDN evaluation, 97 (40%) underwent phone evaluation, 75 (31%) had already established care with an RDN, 41 (17%) underwent in-person evaluation, and 29 (12%) were unable to be contacted. Conclusions: Using electronic screening, 26% of cancer patients are at high risk for MN at diagnosis. Automated RDN review of H-MST screened patients can improve the referral process and optimize limited RDN availability. The current process allows formal RDN evaluations on those with the greatest MN risk. Malnutrition screening protocols focused on the highest risk cancers might further improve this process. More research is needed to optimize RDN staffing and referral practices.